The Outcome of Hospitalized Children with COVID-19 in a Referral Center in Yazd, Iran - Zahra Nafei; Nasrin Behniafard; Mehran Karimi; Mehrdad Shakiba; Abdolhamid Jafari; farzad Ferdosian; Fakhrosadat Azarpeykan; Farimah Shamsi; Alireza Emarati (Patient Safety and Quality Improvement Journal, 2023)
Introduction:As there is limited research on COVID-19 in children, and reports have indicated low adverse clinical outcomes and mortality rates, our team conducted this study to investigate the clinical outcomes in hospitalized children with COVID-19. Materials and Methods: This historical cohort study included children aged 1 month to 18 years with COVID-19. They were admitted to a referral hospital in Yazd, Iran, over a year from February 2020. Demographic information such as age and sex, the length of hospitalization, and the reverse transcription-polymerase chain reaction (PCR) test results were recorded. We also evaluated Patients' outcomes, including admission to the pediatric intensive care unit (PICU), need for mechanical ventilation, and mortality. Results: Our study included 94 patients, of which 52.1% were female and 29.8% were under one year old. Children aged 1-59 months accounted for more than half of the sample (53.2%). The most common symptoms reported were fever (85.1%), respiratory problems (47.9%), and gastrointestinal symptoms (46.8%). The mean duration of hospital stay was 6.4±5.7 days. About 38.3% of cases required admission to the PICU, and 11.7% needed mechanical ventilation. 75% of deaths occurred in children with confirmed COVID-19 who had an underlying disease. Moreover, respiratory distress at the time of referral was significantly associated with admission to the intensive care unit (P=0.008), requiring mechanical ventilation (P=0.003), and mortality (P=0.02). Conclusion:Our findings suggest that children under one year old, patients with underlying diseases, and those experiencing respiratory distress at the time of referral are high-risk groups and require special attention in care and treatment.